Prepreg, preform, fiber reinforced composite material, and manufacturing method thereof
Patent Information
- Application Number
- JP2020567174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-16
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-11-16
AI Technical Summary
【0007】 本発明により、軽量性と力学特性とを高いレベルで両立させた繊維強化複合材料を容易に得ることが可能となる。
Smart Images

Figure 0007639345000003 
Figure 0007639345000004 
Figure 0007639345000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber-reinforced composite material that combines light weight with excellent mechanical properties, and a prepreg for forming the fiber-reinforced composite material. [Background technology]
[0002] Fiber-reinforced composite materials, which use thermosetting or thermoplastic resins as a matrix and combine them with reinforcing fibers such as carbon fiber or glass fiber, are lightweight yet have excellent mechanical properties such as strength and rigidity, as well as flame retardancy and corrosion resistance, and have been applied to many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and construction, electronic devices, industrial machinery, and sporting goods. On the other hand, from the perspective of improving fuel efficiency and portability, further weight reduction is required for components and housings, and porous fiber-reinforced composite materials with internal pores have been developed. However, such porous fiber-reinforced composite materials have a problem in that the mechanical properties dramatically decrease as the proportion of pores is increased for the purpose of weight reduction. For this reason, a technology was required to reduce the weight of fiber-reinforced composite materials while maintaining their mechanical properties.
[0003] As a technique for achieving both weight reduction and mechanical properties of fiber-reinforced composite materials, Patent Document 1 shows a composite structure having reinforcing fibers, resin, and pores, and having protrusions for reinforcement. Patent Document 2 shows a core structure having a zigzag cross section composed of a cured resin and a nonwoven sheet. Patent Document 3 shows a structure composed of paper containing carbon fibers with different diameter cross sections, and a core structure folded so that the cross section has a zigzag cross section. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 117181 [Patent Document 2] Special Publication No. 2012-500864 [Patent Document 3] Special Publication No. 2013-511629. Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, the weight is reduced by increasing the total amount of fine pores, but there is a problem that the mechanical properties are significantly reduced in accordance with the weight reduction. In this case, a reinforcing structure such as a rib or boss is incorporated, but this is a reinforcing structure placed on the surface of the composite structure, and there are problems in that a specific molding die is required and in terms of thinning. In the methods described in Patent Documents 2 and 3, the resin is impregnated without controlling the diameter and amount of the pores, and further, the zigzag structure is easily opened by the load in the bending direction, and is insufficient to achieve both weight reduction and mechanical properties. The object of the present invention is to provide a fiber-reinforced composite material that achieves both light weight and mechanical properties. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention provides a prepreg in which a resin (A) is impregnated into a reinforcing fiber substrate (B), wherein the reinforcing fiber substrate (B) is present in the prepreg in a folded state having a plurality of folds with a folding angle of 0° or more and less than 90°, and a method for producing a prepreg, the method comprising the steps of: step [1]: folding the reinforcing fiber substrate (B) to form a folded state having a plurality of folds with a folding angle of 0° or more and less than 90°; and step [2]: compounding the reinforcing fiber substrate (B) in the folded state with resin (A). Effect of the Invention
[0007] According to the present invention, it is possible to easily obtain a fiber-reinforced composite material that combines light weight with high levels of mechanical properties. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram showing a folded state of a reinforcing fiber substrate (B) in one embodiment of the prepreg of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of a prepreg of the present invention; [Diagram 3] FIG. 3 is an enlarged schematic cross-sectional view of a portion of the prepreg of the embodiment shown in FIG. [Figure 4] Schematic diagram for explaining the folding angle of the reinforcing fiber base material (B) in one embodiment of the prepreg. [Diagram 5] 1 is a schematic cross-sectional view showing one embodiment of a fiber-reinforced composite material of the present invention; [Figure 6] FIG. 1 is an enlarged schematic diagram of the periphery of a reinforcing fiber substrate (B) in one embodiment of the prepreg of the present invention. [Figure 7] FIG. 1 is an enlarged schematic view of a microporous portion in one embodiment of a fiber-reinforced composite material of the present invention. [Figure 8] FIG. 1 is a schematic diagram showing one embodiment of a fiber-reinforced composite material of the present invention. [Figure 9] Schematic diagram showing the folded state of the reinforcing fiber substrate (B) in the prepreg produced in Example 1. [Figure 10] Schematic diagram showing the folded state of the reinforcing fiber substrate (B) in the prepreg produced in Example 5. [Figure 11] Schematic diagram showing the folded state of the reinforcing fiber substrate (B) in the prepreg produced in Comparative Example 1. [Figure 12] Schematic diagram showing one embodiment of the fiber-reinforced composite material produced in Example 3. [Figure 13] FIG. 1 is a schematic diagram showing one embodiment of a fiber-reinforced composite material produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Prepreg> [Reinforced fiber base material (B)] The prepreg of the present invention is characterized in that the reinforcing fiber substrate (B) is present in the prepreg in a folded state with multiple folds with a folding angle of 0° or more and less than 90°. By folding the planar reinforcing fiber substrate (B) with a folding angle of 0° or more and less than 90°, the folding lines try to stretch in an attempt to return to the configuration before folding, that is, the restoring force which is the force in the direction in which the folding angle expands is released, and in molding the prepreg into a fiber-reinforced composite material, an expansion force in the thickness direction of the prepreg can be obtained. The reinforcing fiber substrate (B) in the prepreg becomes the reinforcing fiber (B') in the microporous portion of the fiber-reinforced composite material through the heating and molding.
[0010] Such a prepreg will be described below. The folding angle in this specification is the angle θ formed by a bent portion centered on the folding line 31 of the reinforcing fiber substrate (B) 3 as shown in FIG. 4 when a cross section perpendicular to the folding line direction (hereinafter, unless otherwise specified in this specification, "cross section" means a cross section perpendicular to the folding line direction) is viewed. The folding angle of the reinforcing fiber substrate (B) is preferably 0° or more and 75° or less, more preferably 0° or more and 45° or less, even more preferably 0° or more and 15° or less, and particularly preferably 1° or more and 5° or less. By setting it in such a range, the expansion force during molding into a fiber reinforced composite material can be increased, which is preferable.
[0011] In the cross section of the reinforcing fiber substrate (B), when an arbitrarily selected fold is the first fold, the fold adjacent to the first fold is the second fold, the fold adjacent to the second fold is the third fold, and the fold adjacent to the third fold is the fourth fold, it is preferable that the first fold and any of the folds after the fourth fold are folded in a manner close to each other. By folding in this manner, when the fold is stretched, the area woven between the adjacent folds is likely to form a space, and the coarse pore portion described later is likely to be formed. In this specification, the term "close" is used as a term expressing a concept including the case where they are in contact. In addition, in the following specification, the first fold that is close to the first fold in this manner and the folds after the fourth fold that are closest to the first fold may be simply referred to as "a pair of adjacent folds".
[0012] In this case, when the linear distance between a pair of adjacent folds in the cross section is Lr and the distance between a pair of adjacent folds along the reinforcing fiber substrate (B) is Lf, it is preferable that Lr / Lf is 0.3 or less and Lf is 1 mm or more and 200 mm or less. Lr / Lf is more preferably 0.2 or less, and even more preferably 0.05 or less. Lf is more preferably 1 mm or more and 100 mm or less, even more preferably 2 mm or more and 50 mm or less, and particularly preferably 3 mm or more and 10 mm or less. By setting it in such a range, it is preferable because the pore diameter during molding into a fiber reinforced composite material is easily controlled.
[0013] In the following, for easier understanding, the folded state of the reinforcing fiber substrate (B) in one embodiment of the present invention will be described with reference to the drawings specifically illustrating the folded state of the reinforcing fiber substrate (B) in one embodiment of the present invention. The folded state of the reinforcing fiber substrate (B) in the present invention is not limited by these drawings, but the following description of the specific embodiment can also be understood as a description of the reinforcing fiber substrate (B) in the prepreg of the present invention as a higher concept.
[0014] Fig. 1 is a schematic perspective view of only the reinforcing fiber substrate (B) for explaining the folded state of the reinforcing fiber substrate (B) in the prepreg according to one embodiment of the present invention. Fig. 2 is a schematic cross-sectional view of the prepreg according to the same embodiment, and Fig. 3 is a schematic cross-sectional view of a further enlarged portion of the prepreg.
[0015] In this embodiment, the reinforcing fiber substrate (B) is in a folded state including a Z-shaped structure in which the first fold and one of the second folds adjacent to the first fold are bending points when an arbitrarily selected fold is the first fold in the cross section. For example, when the fold indicated by 31A in FIG. 3 is the first fold, the reinforcing fiber substrate (B) is folded to form a Z-shaped structure in which the first fold and one of the second folds adjacent to the first fold are bending points indicated by 31B in the cross section. By forming such a folded structure, a force that causes the Z-shaped structure to expand vertically is generated, which facilitates the formation of the coarse pores described later. When the reinforcing fiber substrate (B) is in a folded state in which such a Z-shaped structure is continuously formed, a large restoring force can be obtained as a whole.
[0016] More specifically, in this embodiment, the reinforcing fiber substrate (B) has a folded structure including a substantially triangular structure formed by the first fold and one of the fourth folds coming close to each other when a certain fold is defined as a first fold, two folds adjacent to both sides of the first fold are defined as second folds, two folds adjacent to the second fold are defined as third folds, and two folds adjacent to the outside of the third fold are defined as fourth folds. For example, if the fold indicated by 31A in FIG. 3 is defined as the first fold, one of the second folds is defined as 31B, one of the third folds is defined as 31C, and one of the fourth folds is defined as 31D, and the reinforcing fiber substrate (B) has a folded structure including a substantially triangular structure formed by the first fold 31A and the fourth fold 31D coming close to each other. Here, the first fold 31A and the fourth fold 31D may be in contact with each other or may be spaced apart to some extent. That is, following the above description, in this embodiment, the fold 31A and the fold 31D are a pair of adjacent folds. In the former case, the contact point between the first fold 31A and the fourth fold 31D, the second fold 31B, and the third fold 31C form an approximately triangular structure, and in the latter case, the first fold 31A and the fourth fold 31D are spaced apart to form an approximately triangular structure with one end open. In this specification, the term "approximately triangular" is used as a term that includes such structures. By forming such a folding structure, a force that tends to expand the approximately triangular structure vertically is generated, and a restoring force can be obtained.
[0017] Furthermore, in this embodiment, as shown in Fig. 2, the reinforcing fiber base material (B) has a folding structure in which the folding structure including the approximately triangular structure is inverted and continuous. By having such a regular folding structure, it becomes easy to control the expansion force in a desired direction. In addition to this embodiment, in the prepreg of the present invention, it is preferable that the reinforcing fiber base material (B) has a regular folding structure throughout the entire prepreg in order to obtain a uniform expansion force.
[0018] In this embodiment, it is preferable that Lr / Lf is 0.3 or less and Lf is 1 mm or more and 200 mm or less, where Lr is the linear distance between the first fold and the fourth fold adjacent to the first fold, and Lf is the distance from the first fold to the fourth fold along the reinforcing fiber substrate (B). As shown in FIG. 3, Lr is the shortest distance between the surfaces of the reinforcing fiber substrate (B) at a pair of adjacent folds. Lf corresponds to the length of the reinforcing fiber substrate (B) between a pair of adjacent folds, that is, from the first fold 31A to the fourth fold 31D in FIG. 3. Lr / Lf is preferably 0.2 or less, more preferably 0.05 or less. Lf is more preferably 1 mm or more and 100 mm or less, even more preferably 2 mm or more and 50 mm or less, and particularly preferably 3 mm or more and 10 mm or less. By setting the ratio of Lr to Lf in this range, the restoring forces in the in-plane direction are cancelled out, making it easier to suppress expansion in the in-plane direction, making it easier to form coarse pores having a perimeter corresponding to Lf, and making it easier to control the pore size of the coarse pores.
[0019] In the present invention, examples of the reinforcing fibers contained in the reinforcing fiber substrate (B) include carbon fibers, glass fibers, metal fibers, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, and basalt fibers. These may be used alone or in combination of two or more types as appropriate. Among these, the reinforcing fibers are preferably carbon fibers from the viewpoint of light weight and excellent mechanical properties. The reinforcing fibers preferably have an elastic modulus of 200 GPa or more. In addition, the reinforcing fibers are preferably carbon fibers, and carbon fibers having an elastic modulus of 200 GPa or more are particularly preferable.
[0020] In the present invention, the reinforcing fibers constituting the reinforcing fiber substrate (B) are preferably discontinuous fibers, more specifically, the number average fiber length is preferably 1 mm or more and 50 mm or less, more preferably 3 mm or more and 20 mm or less, and even more preferably 4 mm or more and 10 mm or less. By setting it in such a range, it is possible to achieve both the ease of folding of the reinforcing fiber substrate (B) and the high folding recovery force at a high level, which is preferable. The number average fiber length here can be obtained by randomly selecting 400 single yarns of the reinforcing fibers constituting the reinforcing fiber substrate (B) and calculating the arithmetic average value of their fiber lengths.
[0021] Furthermore, the reinforcing fiber substrate (B) is preferably a nonwoven fabric composed of discontinuous reinforcing fibers. The nonwoven fabric can be produced by an airlaid method, a carding method, a papermaking method, or the like. In such a nonwoven fabric, the reinforcing fibers are preferably randomly dispersed. By dispersing the reinforcing fibers randomly, it is preferable that a prepreg having small concentration unevenness between the resin (A) and the reinforcing fiber substrate (B) and excellent isotropy can be obtained.
[0022] In the prepreg of the present invention, the reinforcing fiber substrate (B) is preferably 10 parts by mass or more and 100 parts by mass or less, and more preferably 20 parts by mass or more and 50 parts by mass or less, when the resin (A) is 100 parts by mass. If it is less than this range, the reinforcing effect of the reinforcing fiber substrate (B) may be insufficient. If it is more than this range, the weight reduction effect of the reinforcing fiber may be insufficient.
[0023] Resin (A) In the prepreg of the present invention, the resin (A) is a resin impregnated into the reinforcing fiber substrate (B), more specifically, a resin impregnated into the entirety including both the inside of the reinforcing fiber substrate (B) and the spaces formed between the reinforcing fiber substrates (B) by folding the reinforcing fiber substrate (B) described above.
[0024] The resin (A) may be a thermoplastic resin or a thermosetting resin, but is preferably a thermoplastic resin. When the resin (A) is a thermosetting resin, it has excellent heat resistance, but if the resin (A) hardens at the prepreg stage, it may not be preferable. The prepreg is composed of the resin (A) and the reinforcing fiber substrate (B) which is a sheet-like reinforcing fiber, but if the resin (A) hardens, the restoring force of the folded structure of the reinforcing fiber substrate (B) of the prepreg may not be expressed. By using a thermoplastic resin as the resin (A), the melting and softening of the resin (A) during hot molding can be stably performed, and a fiber reinforced composite material with excellent light weight can be obtained, which is preferable.
[0025] Examples of thermoplastic resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyolefins such as polyethylene, polypropylene, polybutylene, and modified polypropylene, polyamides such as polyoxymethylene, polyamide 6, and polyamide 66, polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyarylene sulfides such as polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamideimide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyarylene ether ketones such as polyketone, polyether ketone, polyether ether ketone, and polyether ketone ketone, polyarylate, polyether nitrile, and phenoxy resin. These thermoplastic resins may be copolymers, modified bodies, and / or resins blended with two or more kinds.
[0026] Among these, in terms of the balance between moldability, heat resistance, and mechanical properties, the thermoplastic resin is more preferably at least one selected from the group consisting of polyolefin, polycarbonate, polyester, polyarylene sulfide, polyamide, polyoxymethylene, polyetherimide, polyethersulfone, and polyarylene ether ketone, and further preferably polypropylene in terms of productivity and cost.
[0027] In addition, the prepreg of the present invention is excellent in the freedom of selection of the resin (A) since it is possible to expand using the restoring force of the reinforcing fiber base material (B) contained therein. For example, if a resin with high heat resistance, i.e., a high melting point, is selected as the resin (A), a high processing temperature is also required. In this case, undesirable side effects such as thermal decomposition and oxidative deterioration may occur, inhibiting the expansion and reducing the moldability into a desired shape. On the other hand, the prepreg of the present invention is excellent in the expansion force even at high temperatures because the reinforcing fiber base material (B) contained therein exhibits a high restoring force. From this viewpoint, it is more preferable that the resin (A) is at least one selected from the group consisting of polyamide, polyarylene sulfide, and polyarylene ether ketone, and it is even more preferable that the resin is polyarylene sulfide or polyarylene ether ketone.
[0028] Resin (A) may further contain other fillers and additives as appropriate depending on the application, etc., within the scope of the object of the present invention. Examples include inorganic fillers, flame retardants, conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, coupling agents, etc.
[0029] The melting point of the thermoplastic resin used as resin (A) is preferably 100°C or higher and 400°C or lower, more preferably 120°C or higher and 300°C or lower, and even more preferably 140°C or higher and 250°C or lower. By setting the temperature in this range, it is possible to achieve both the molding processability into a fiber reinforced composite material and the heat resistance of the resulting fiber reinforced composite material, which is preferable. In addition, the glass transition temperature of the thermoplastic resin used as resin (A) is preferably 0°C or higher and 250°C or lower, more preferably 50°C or higher and 200°C or lower, and even more preferably 100°C or higher and 160°C or lower. In particular, when resin (A) is an amorphous thermoplastic resin, it is preferable to set the glass transition temperature of the thermoplastic resin in this range, because it is possible to achieve both the molding processability into a fiber reinforced composite material and the heat resistance of the resulting fiber reinforced composite material.
[0030] <Prepreg manufacturing method> The prepreg of the present invention can be produced, for example, by a production method having the following steps [1] and [2] in this order. Step [1]: folding the reinforcing fiber substrate (B) into a folded state having a plurality of folds with folding angles of 0° or more and less than 90°; Step [2]: A step of compounding the resin (A) with the folded reinforcing fiber base material (B).
[0031] In step [1], the reinforcing fiber substrate (B) is folded into the above-mentioned folded state. In general, the higher the elastic modulus of a reinforcing fiber, the lower the elongation and the more likely it is to break when bent. By folding the reinforcing fiber substrate (B) in advance in step [1], the curvature of the reinforcing fiber monofilament is suppressed by the voids between the reinforcing fibers, making it possible to fold the substrate while suppressing breakage of the fibers.
[0032] In step [2], the method of compounding the resin (A) with the reinforcing fiber substrate (B) includes a method of directly injecting the molten resin (A) into the reinforcing fiber substrate (B), and a method of compounding the film-like, powder-like, or fibrous resin (A) with the reinforcing fiber substrate (B) and impregnating it by heating and melting it. From the viewpoint of ease of production, a method of impregnating the reinforcing fiber substrate (B) with pressure while the resin (A) is heated to a temperature at which it melts or softens is applied is desirable. As equipment for realizing such an impregnation method, a press molding machine or a double belt press machine can be suitably used. In the case of a batch type, the former is used, and productivity can be improved by using an intermittent press system in which two or more machines for heating and cooling are arranged in parallel. In the case of a continuous type, the latter is used, and continuous processing can be easily performed, so that continuous productivity is excellent.
[0033] <Method of manufacturing fiber-reinforced composite materials> The fiber reinforced composite material of the present invention can be manufactured by heating the prepreg described above to a temperature at which the resin (A) melts or softens, and molding it. When the resin (A) is heated to a temperature at which the resin (A) melts or softens and softens, the restoring force that causes the folded structure of the reinforcing fiber substrate (B) to return to the structure before folding, that is, the force in the direction in which the folding angle expands, is released. This restoring force becomes an expansion force in the thickness direction of the prepreg, and the prepreg expands in a manner in which the reinforcing fiber substrate (B) is pushed up by the reinforcing fiber substrate (B) due to this expansion force. FIG. 5 is a cross-sectional schematic diagram showing an example of a fiber reinforced composite material molded using the prepreg shown in FIG. 2. In this way, when the prepreg is heated and the resin (A) softens, the reinforcing fiber substrate (B) deforms in the direction in which the folding angle of the reinforcing fiber substrate (B) expands, and the prepreg expands. Typically, as shown in FIG. 5, this expansion forms a void portion 4.
[0034] Specifically, when the resin (A) is a crystalline thermoplastic resin, the temperature at which the resin (A) melts or softens may be any temperature higher than the melting point, but is preferably a temperature 20° C. or higher than the melting point. When the resin (A) is an amorphous thermoplastic resin, the temperature may be any temperature higher than the glass transition temperature, but is preferably a temperature 20° C. or higher than the glass transition temperature. As the upper limit temperature, it is preferable to apply a temperature equal to or lower than the thermal decomposition temperature of the resin (A).
[0035] In addition, in molding, it is preferable to adjust the thickness of the prepreg expanded by heating. As a method for controlling the thickness, any method can be used as long as the obtained fiber reinforced composite material can be controlled to the desired thickness, but a method of constraining the thickness using a metal plate or a method of directly controlling the thickness by adjusting the pressure are preferable from the viewpoint of ease of production. As equipment for realizing such a method, a press molding machine or a double belt press machine can be suitably used. In the case of a batch type, the former is used, and productivity can be improved by using an intermittent press system in which two or more machines for heating and cooling are arranged in parallel. In the case of a continuous type, the latter is used, and continuous processing can be easily performed, resulting in excellent continuous productivity.
[0036] <Fiber-reinforced composite materials> In a preferred embodiment, the fiber-reinforced composite material produced as described above has coarse pores formed by the restoring force of the folded structure of the reinforcing fiber substrate (B) as described above to expand. Fig. 5 is a cross-sectional schematic diagram showing an example of a fiber-reinforced composite material molded using the prepreg shown in Fig. 2. The prepreg is heated to melt or soften the resin (A), and the restoring force of the folded structure of the reinforcing fiber substrate (B) is released. This restoring force becomes an expansion force in the thickness direction of the prepreg, and this expansion force forms coarse pores that are substantially surrounded by the reinforcing fiber substrate (B).
[0037] Therefore, the folding structure of the reinforcing fiber base material is substantially the same as the folding structure of the prepreg described above, and the explanation of the folding structure is in accordance with the description of the prepreg described above. However, when molding is performed using the prepreg described above, the folding angle of the reinforcing fiber base material (B) becomes large by molding.
[0038] The coarse pores substantially surrounded by the reinforcing fiber substrate (B) in the folded state are spaces partitioned only by the reinforcing fiber substrate (B) impregnated with the resin (A) and folded, or by the reinforcing fiber substrate (B) impregnated with the resin (A) and the resin (A) present between adjacent folds of the reinforcing fiber substrate (B), as shown in FIG. 5, and are illustrated as a substantially triangular space 4 in FIG. 5. In this embodiment, the folds may become unclear due to the pressure during expansion, and a substantially circular or elliptical space may be formed. In this embodiment, the coarse pores are formed as hollow spaces with the folds of the reinforcing fiber substrate (B) as the longitudinal direction.
[0039] The coarse pores preferably have an average maximum length of the openings in the cross section of 500 μm or more. Here, the maximum length of the cross-sectional openings is the maximum length that can be drawn in a straight line within the openings in the cross section of the fiber-reinforced composite material. If the average maximum length of the openings is 500 μm or more, a significant weight reduction effect can be obtained. The average maximum length of the cross-sectional openings of the coarse pores is preferably 1000 μm or more and 10000 μm or less, more preferably 1500 μm or more and 6500 μm or less, and even more preferably 2500 μm or more and 4500 μm or less.
[0040] Moreover, the coarse pore portion preferably has a structure in which a pair of adjacent folds 31 of the reinforcing fiber substrate (B) are bonded by the resin (A) as shown in Fig. 5. With such a structure, deformation due to opening at a pair of adjacent folds is suppressed when a load is applied to the fiber reinforced composite material.
[0041] In a more preferred embodiment, the fiber-reinforced composite material has a microporous structure 5 in the resin (A) 2 impregnated in the reinforcing fiber substrate (B) 3, as shown in Fig. 8. This embodiment will be described below.
[0042] FIG. 6 is a schematic diagram showing an embodiment of the reinforcing fiber substrate (B) included in the prepreg described above, enlarged together with the resin (A) impregnated therein. In this embodiment, the reinforcing fiber substrate (B) is a nonwoven fabric composed of discontinuous reinforcing fibers. The reinforcing fiber substrate (B) is impregnated with the resin (A) and in a compressed state, and springs back when the resin (A) melts or softens and the compressed state is released. This springback forms fine pores in the resin (A) between the reinforcing fibers, as shown in FIG. 7. That is, a microporous structure is formed in the resin (A) impregnated in the reinforcing fiber substrate (B). Hereinafter, the part in which the microporous structure is formed in the resin (A) impregnated in such a reinforcing fiber substrate (B) is referred to as a "microporous portion".
[0043] The microporous portion preferably has an average pore diameter of 200 μm or less as measured by mercury intrusion porosimetry. The average pore diameter is preferably 10 μm or more and 150 μm or less, more preferably 30 μm or more and 100 μm or less. If it is smaller than this range, the weight reduction effect may not be sufficient, and if it is larger than this range, the mechanical properties may deteriorate. Mercury intrusion porosimetry is a method for measuring pore diameter using a mercury intrusion porosimeter, in which mercury is injected into a sample at high pressure, and the pore diameter can be calculated from the applied pressure and the amount of mercury injected. The average pore diameter is a value that can be calculated from the following formula (1). (Average pore diameter) = 4 × (pore volume) / (specific surface area) Equation (1).
[0044] The specific gravity of the microporous portion is 0.3 g / cm 3 More than 0.8g / cm 3 It is preferable that the concentration is 0.4 g / cm or less. 3 More than 0.7g / cm 3 It is more preferable that the specific gravity is equal to or less than this range. If the specific gravity is smaller than this range, the mechanical properties may be deteriorated, and if the specific gravity is larger than this range, the weight reduction effect may be insufficient. The specific gravity here is calculated by multiplying the mass [g] of a sample cut out of only the microporous portion by the volume [cm3] calculated from the shape of the sample. 3 ] and is the arithmetic mean of the specific gravity measured on five randomly selected samples.
[0045] The final fiber-reinforced composite material as a whole has a specific gravity of 0.001 g / cm 3 More than 0.2g / cm 3 It is preferable that the concentration is 0.01 g / cm or less. 3 More than 0.15g / cm 3 More preferably, it is 0.01 g / cm or less. 3 More than 0.1g / cm 3 It is more preferable that the specific gravity is 0.1 g / cm or less. If the specific gravity is less than this range, the mechanical properties may be insufficient. If the specific gravity is more than this range, the weight reduction effect may be insufficient. 3In the following cases, it is generally difficult to realize mechanical properties, and the effects of the present invention can be efficiently achieved. The specific gravity here is calculated by multiplying the sample mass [g] by the volume [cm3] calculated from the sample shape. 3 ] is the value divided by
[0046] The thickness of the fiber-reinforced composite material is preferably 0.1 mm or more and 5 mm or less, and more preferably 0.6 mm or more and 3 mm or less. By setting the thickness in this range, the effect of the present application, which is light weight and excellent mechanical properties even with a thin wall, can be efficiently exhibited, which is preferable. In particular, fiber-reinforced composite materials having pores tend to be difficult to maintain pressure in a process of pressing other materials, such as a press process. The fiber-reinforced composite material of the present application, which achieves both light weight and mechanical properties by controlling the pores, is preferable because it can be suitably applied to such a pressing process.
[0047] Furthermore, the fiber reinforced composite material of the present invention preferably has a structure in which the cross-sectional openings of the coarse pores are aligned in the in-plane direction, and may be a laminate in which a plurality of layers of the structure derived from the prepreg having such a structure are laminated. Such a laminate is preferable because it is easy to obtain a molded product with a thick wall or uneven wall thickness. It is more preferable that the layers aligned with the cross-sectional openings of the coarse pores have a laminate structure in which the extension direction of the cross-sectional openings of the coarse pores is changed for each layer, and it is even more preferable that the layers are laminated so that the extension direction of the cross-sectional openings of the coarse pores is perpendicular to each other for each layer. In this case, the contents described using the extension direction of the cross-sectional openings of the coarse pores in the above description of the fiber reinforced composite material of the present invention should be understood as a description for each layer. The number of layers is preferably 2 to 50, more preferably 2 to 10.
[0048] There is no particular restriction on the lamination method, and examples thereof include a method of heating the prepregs after lamination, and a method of laminating fiber-reinforced composite materials that have been heated and molded in advance. There is no particular restriction on the bonding between the layers during lamination, and examples thereof include bonding with an adhesive and heat welding. In particular, the prepregs and fiber-reinforced composite materials of the present invention, which have excellent expansive force as described above, are preferred because they have excellent pore retention ability even in the heating and pressurizing process during heat welding. Note that a preform formed by laminating the above-mentioned prepregs to obtain such a laminated fiber-reinforced composite material is also one aspect of the present invention.
[0049] <Sandwich structure> The fiber-reinforced composite material of the present invention is also preferably formed into a sandwich structure in which skin layers made of another fiber-reinforced resin are arranged on both sides of the fiber-reinforced composite material. Preferably, the skin layers are layers having a higher elastic modulus than the fiber-reinforced composite material. There are no particular limitations on the method for joining the skin layers, and examples include joining with an adhesive and heat welding. In particular, the fiber-reinforced composite material of the present invention and its laminate, which are excellent in the above-mentioned expansive force, are preferable because they have excellent pore retention ability even in the heating and pressurizing process during heat welding.
[0050] The reinforcing fibers contained in the fiber-reinforced resin of the skin layer can be suitably the same as those of the reinforcing fiber base material (B) described above, and carbon fibers are preferred from the viewpoints of light weight, mechanical properties, and economic efficiency. The reinforcing fibers constituting the fiber-reinforced resin of the skin layer preferably have a number average fiber length of 100 mm or more, and preferably 150 mm or more. There is no particular upper limit on the length of the reinforcing fibers, and the reinforcing fibers may be continuous over the entire width of the skin layer in the fiber orientation direction, or may be interrupted along the way. From the viewpoint of the mechanical properties of the sandwich structure, it is preferable that the continuous reinforcing fibers are arranged in one direction. Also, from the viewpoint of isotropy of the mechanical properties, it is particularly preferable that the skin layer has a structure in which a plurality of fiber-reinforced resin layers in which reinforcing fibers are arranged in one direction are laminated while changing the lamination angle, that is, while changing the arrangement direction of the reinforcing fibers in each layer.
[0051] The resin contained in the fiber-reinforced resin of the skin layer is preferably a thermosetting resin. Examples of the thermosetting resin include unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol resin, urea resin, melamine resin, thermosetting polyimide resin, cyanate ester resin, bismaleimide resin, benzoxazine resin, copolymers, modified products thereof, and resins obtained by blending at least two of these. Among these, the thermosetting resin is preferably an epoxy resin, which has excellent mechanical properties, heat resistance, and adhesion to reinforcing fibers. EXAMPLES
[0052] The materials used in the examples and comparative examples are as follows.
[0053] [PP resin] A crystalline polypropylene resin composition was used, which consisted of 80% by mass of polypropylene (Prime Polypro (registered trademark) J105G manufactured by Prime Polymer Co., Ltd.) and 20% by mass of acid-modified polypropylene (Admer QB510 manufactured by Mitsui Chemicals, Inc.), and had a melting point of 160°C measured in accordance with JIS K7121 (2012). The polypropylene resin composition was produced by mixing the thermoplastic resins polypropylene and acid-modified polypropylene as raw materials in the above-mentioned mass ratio, and melt-kneading the mixture in a twin-screw extruder with a cylinder temperature of 200°C to produce resin pellets. The resin pellets were then press-molded using a press molding machine adjusted to a mold surface temperature of 180°C and a film thickness of 0.22 mm, to produce a film having a basis weight of 200 g / cm. 2 A PP resin film was produced.
[0054] [PC resin] The polycarbonate resin used was an amorphous thermoplastic resin made of polycarbonate ("Iupilon" (registered trademark) H-4000 manufactured by Mitsubishi Engineering Plastics Corporation) with a glass transition temperature of 150°C measured according to JIS K7121 (2012). The resin pellets of the thermoplastic resin polycarbonate were press molded using a press molding machine adjusted to a mold surface temperature of 240°C and a film thickness of 0.17 mm, to give a film with a basis weight of 200 g / cm. 2 A PC resin film was produced.
[0055] [PA resin] A crystalline polyamide resin was used, consisting of polyamide 6 (Toray Industries, Inc.'s "Amilan" (registered trademark) CM1017) with a melting point of 225°C measured according to JIS K7121 (2012). The resin pellets of polyamide, a thermoplastic resin, were press molded using a press molding machine adjusted to a mold surface temperature of 260°C and a film thickness of 0.18 mm, to obtain a film with a basis weight of 200 g / cm. 2 A PA resin film was produced.
[0056] [PPS resin] A crystalline polyarylene sulfide resin was used, which is made of polyphenylene sulfide ("TORELINA" (registered trademark) A900 manufactured by Toray Industries, Inc.) and has a melting point of 278°C measured in accordance with JIS K7121 (2012). A resin pellet of polyarylene sulfide, which is a thermoplastic resin, was press molded using a press molding machine adjusted to a mold surface temperature of 300°C and a film thickness of 0.15 mm, and a basis weight of 200 g / cm was obtained. 2 A PPS resin film was produced.
[0057] [PEKK resin] A crystalline polyarylene ether ketone resin was used, which is made of polyether ketone ketone ("KEPSTAN" (registered trademark) 6002 manufactured by Arkema) and has a melting point of 305°C measured in accordance with JIS K7121 (2012). Resin pellets of polyarylene ether ketone, a thermoplastic resin, were press-molded using a press molding machine adjusted to a mold surface temperature of 350°C and a film thickness of 0.16 mm, to give a film with a basis weight of 200 g / cm. 2 A PEKK resin film was produced.
[0058] [Carbon fiber nonwoven fabric] A carbon fiber bundle with a total of 12,000 single fibers was obtained by spinning, calcining, and surface oxidation of a copolymer mainly composed of polyacrylonitrile. The properties of this carbon fiber bundle were a tensile modulus of 220 GPa measured in accordance with JIS R7608 (2007), and a circular cross section with a single fiber diameter of 7 μm.
[0059] The carbon fiber bundle was cut into 6 mm lengths with a cartridge cutter to obtain chopped carbon fibers. A dispersion liquid with a concentration of 0.1% by mass was prepared from water and a surfactant (Polyoxyethylene lauryl ether (trade name) manufactured by Nacalai Tesques Co., Ltd.), and a carbon fiber substrate was prepared using this dispersion liquid and chopped carbon fibers. The manufacturing device is equipped with a cylindrical container with a diameter of 1000 mm having an opening and closing cock at the bottom of the container as a dispersion tank, and a linear transport section (inclined angle 30°) connecting the dispersion tank and the papermaking tank. A stirrer is attached to the opening on the top surface of the dispersion tank, and chopped carbon fiber and dispersion liquid (dispersion medium) can be charged from the opening. The papermaking tank is equipped with a mesh conveyor with a papermaking surface with a width of 500 mm at the bottom, and a conveyor capable of transporting the carbon fiber substrate (papermaking substrate) is connected to the mesh conveyor. Papermaking was performed with a carbon fiber concentration in the dispersion liquid of 0.05% by mass. The carbon fiber substrate was dried in a drying oven at 200°C for 30 minutes to obtain a carbon fiber nonwoven fabric composed of discontinuous reinforcing fibers in which the orientation direction of the carbon fiber single yarns was randomly distributed. The obtained carbon fiber nonwoven fabric was observed using a laser microscope (Keyence Corporation, VK-9510), and the fiber lengths of a total of 400 reinforcing fibers were measured using the software attached to the device. The number-average fiber length of the reinforcing fibers calculated as the arithmetic average value was 6 mm.
[0060] [Thermosetting prepreg used for skin layer] A carbon fiber bundle with a total of 12,000 single fibers was obtained by spinning, calcining, and surface oxidation of a copolymer mainly composed of polyacrylonitrile. The properties of this carbon fiber bundle were a tensile modulus of 220 GPa measured in accordance with JIS R7608 (2007), and a circular cross section with a single fiber diameter of 7 μm.
[0061] Epoxy resins (30 parts by mass of "Epikote (registered trademark)" 828, manufactured by Japan Epoxy Resins Co., Ltd., 35 parts by mass of "Epikote (registered trademark)" 1001, and 35 parts by mass of "Epikote (registered trademark)" 154) were heated and kneaded in a kneader to uniformly dissolve the polyvinyl formal (5 parts by mass of "Vinylec (registered trademark)" K, manufactured by Chisso Corporation), and then 3.5 parts by mass of a curing agent, dicyandiamide (DICY7, manufactured by Japan Epoxy Resins Co., Ltd.), and 7 parts by mass of a curing agent, 4,4-methylenebis(phenyldimethylurea) ("Omicure (registered trademark) 52, manufactured by PTI Japan Co., Ltd.), were added and kneaded in a kneader to prepare an uncured epoxy resin composition. From this, a coating weight of 132 g / m was applied using a knife coater. 2 An epoxy resin film was prepared.
[0062] Then, a sheet with carbon fiber bundles oriented in one direction was prepared, and epoxy resin films were placed on both sides of the sheet. The sheet was then impregnated with epoxy resin by heating and pressurizing, resulting in a carbon fiber mass per unit area of 125 g / m. 2 The thermosetting prepreg had a fiber volume content of 60% and a thickness of 0.125 mm.
[0063] The methods for evaluating the structure, physical properties, etc. in each of the examples and comparative examples are as follows.
[0064] [Evaluation of folding angles] A sample was cut out from the prepreg so that the cross section perpendicular to the creases of the carbon fiber nonwoven fabric was the observation surface, and polished so that the cross section of the creases of the carbon fiber nonwoven fabric could be observed. The obtained sample was observed with a laser microscope (Keyence Corporation, VK-9510), and angles were measured in the observed image using software attached to the device, and the angle θ of the bent part with the crease 31 of the carbon fiber nonwoven fabric 3 as the center was obtained for each crease, as shown in Figure 4. The fold angles were obtained for a total of 20 creases, and the arithmetic average value was calculated.
[0065] [Evaluation of Lr and Lf] A sample was cut out from the prepreg so that the cross section perpendicular to the creases of the carbon fiber nonwoven fabric was the observation surface, and polished so that a pair of adjacent creases of the carbon fiber nonwoven fabric and a cross section of the continuous carbon fiber nonwoven fabric connecting the adjacent pair of creases could be observed. The obtained sample was observed with a laser microscope (Keyence Corporation, VK-9510), and the length of the observed image was measured using the software attached to the device to determine the linear distance (Lr) between the adjacent pair of creases and the distance (Lf) connecting the adjacent pair of creases along the carbon fiber nonwoven fabric. Lr, Lf and Lr / Lf were obtained for a total of 20 adjacent creases, and the arithmetic average value was calculated.
[0066] [Evaluation of large pores] A sample was cut out from the fiber-reinforced composite material so that the cross section parallel to the thickness direction was the observation surface, and polished so that a pair of adjacent folds of the carbon fiber nonwoven fabric and a cross section where the continuous carbon fiber nonwoven fabric connects between the pair of adjacent folds could be observed. The obtained sample was observed with a laser microscope (Keyence Corporation, VK-9510) to observe the cross section of the coarse pores as a planar cross section opening. The length was measured using the software attached to the device, and the maximum straight line length that could be drawn within the cross section opening was obtained. Measurements were performed on a total of 20 cross section openings, and the arithmetic average value was taken as the maximum length of the cross section opening. For the value used for the arithmetic average, the measurement results of adjacent cross section openings and samples spaced 5 cm or more apart in the depth direction were used.
[0067] [Evaluation of average pore diameter] The pore size was measured at mercury intrusion pressures ranging from 4 kPa to 400 MPa using an Autopore IV9510 manufactured by Micromeritics as a mercury intrusion porosimeter. The average pore diameter was calculated from the pore volume and specific surface area obtained as the measurement results using formula (1). (Average pore diameter) = 4 × (pore volume) / (specific surface area) Equation (1).
[0068] [Evaluation of specific gravity of microporous part] The specific gravity of the microporous portion was calculated by cutting out a sample from the fiber-reinforced composite material and multiplying the sample mass [g] by the volume [cm3] obtained from the outer circumference of the sample. 3 ] and is obtained by taking the arithmetic average of the specific gravity measured on five randomly selected samples.
[0069] [Evaluation of specific gravity of fiber-reinforced composite materials] The specific gravity of a fiber-reinforced composite material is calculated by multiplying the mass [g] of the fiber-reinforced composite material by the volume [cm3] calculated from the perimeter of the fiber-reinforced composite material. 3 ] can be calculated by dividing the value by
[0070] [Evaluation of deflection under load] The test machine used was an Instron (registered trademark) 5565 type universal material testing machine (manufactured by Instron Japan Co., Ltd.). A sample was placed on a lower indenter having a square inner diameter with one side of 100 mm so as to cover the inner diameter, and a plane area of 10 mm2 was measured from directly above the intersection of the diagonals of the square inner diameter. 2 A load was gradually applied using a cylindrical upper indenter, and the deflection [mm] was calculated by subtracting the displacement at a load of 0.1 N (at the start of contact) from the displacement at a load of 50 N. The specimen was then evaluated on a three-point scale, with good and fair being considered pass. Good: Deflection is 2mm or less. fair: The deflection is greater than 2 mm and less than 3 mm. Bad: Deflection is greater than 3 mm.
[0071] The prepregs, fiber-reinforced composite materials, and sandwich structures produced in the examples and comparative examples will be described below.
[0072] [Example 1] The carbon fiber nonwoven fabric prepared as above was used as the reinforcing fiber substrate (B). The prepreg was folded regularly over the entire surface to have the cross-sectional structure shown in FIG. 9. The fabric had a basis weight of 100 g / cm. 2A folded base material of the above was prepared. In this case, when the prepreg was made, in a pair of adjacent folds 6 of the reinforcing fiber base material (B), one of the first fold and the fourth fold was folded in the form of being closest to each other, and the linear distance (Lr) between the pair of adjacent folds was 0 mm, that is, the pair was folded so as to be in contact, and the distance (Lf) between the pair of adjacent folds along the carbon fiber nonwoven fabric, which is the reinforcing fiber base material (B), was 10 mm. Furthermore, the folded base material was folded so that the composition ratio 7 of the pair of adjacent folds when viewed from both sides was a symmetrical structure.
[0073] That is, on one side, a pair of adjacent folds on the other side is arranged midway between a pair of adjacent folds on the other side and the pair of adjacent folds arranged next to the pair of adjacent folds on the other side, and the folded state is repeated. In other words, the reinforcing fiber substrate (B) is in a folded state including a structure in which a Z-shaped structure having a first fold and one of the second folds adjacent to the first fold as bending points is continuous.
[0074] The reinforcing fiber substrate (B) is in a folded state including a substantially triangular structure formed by a pair of adjacent folds, and the folded structure including the substantially triangular structure has a continuous folded structure while being inverted.
[0075] Next, the carbon fiber nonwoven fabric was coated with resin (A) having a basis weight of 200 g / cm 2 The PP resin film was laminated and then hot-pressed. In the hot-press process, the mold temperature was 180°C and pressure was 3 MPa for 10 minutes to impregnate the carbon fiber nonwoven fabric with the PP resin, resulting in a prepreg with a side length of 200 mm.
[0076] A fiber-reinforced composite material was molded by heating and expanding one sheet of the obtained prepreg for 10 minutes using a press molding machine adjusted to a mold surface temperature of 180°C and a molded product thickness of 2.8 mm. The obtained fiber-reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in Figure 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0077] [Example 2] As the reinforcing fiber substrate (B), except that the configuration of the folded substrate was changed so that Lr was 1 mm and Lf was 9 mm, processing was performed in the same manner as in Example 1 to obtain a prepreg and a fiber reinforced composite material. The obtained fiber reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in FIG. 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0078] [Example 3] As the reinforcing fiber substrate (B), except that the configuration of the folded substrate was changed so that Lr was 2 mm and Lf was 8 mm, processing was performed in the same manner as in Example 1 to obtain a prepreg and a fiber reinforced composite material. The obtained fiber reinforced composite material had an opening with a cross section of approximately trapezoidal shape with three sides constituted by micropores as shown in FIG. 12. The openings of the vacant coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0079] [Example 4] As the reinforcing fiber substrate (B), a folded substrate similar to that in Example 1 was used, and as the resin (A), a fiber having a basis weight of 200 g / cm 2 The PC resin film was laminated and hot-pressed. In the hot-pressing process, the PC resin was impregnated into the carbon fiber nonwoven fabric by pressing at a mold temperature of 240°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side of 200 mm. One sheet of the obtained prepreg was heated and expanded for 10 minutes using a press molding machine adjusted to a mold temperature of 240°C and a molded product thickness of 2.2 mm, to mold a fiber-reinforced composite material. The obtained fiber-reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in FIG. 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0080] [Example 5] As the reinforcing fiber substrate (B), a carbon fiber nonwoven fabric was folded regularly over the entire prepreg so as to have the cross-sectional structure shown in FIG. 10, and the basis weight was 100 g / cm. 2A folded base material of the above was prepared. In this case, when the prepreg was made, in a pair of adjacent folds 6 of the reinforcing fiber base material (B'), one of the first fold and the fourth fold was folded in the form of being closest to each other, and the linear distance (Lr) between the adjacent pair of folds was 0 mm, that is, the pair was folded so that they were in contact, and the length (Lf) between the adjacent pair of folds along the carbon fiber nonwoven fabric, which is the reinforcing fiber base material (B), was 10 mm. Furthermore, the folded base material was folded so that the composition ratio 7 of the adjacent pair of folds when viewed from the front and back was asymmetrical. In other words, the folded base material was folded so that the adjacent pair of folds on one side was arranged at a position where the distance between the adjacent pair of folds and the adjacent pair of folds arranged next to it was divided into 1:4, and the adjacent pair of folds on the other side were arranged and repeated. In other words, the reinforcing fiber substrate (B) is in a folded state including a continuous Z-shaped structure having a first fold and one of the second folds adjacent to the first fold as bending points.
[0081] The reinforcing fiber substrate (B) is in a folded state including a substantially triangular structure formed by a pair of adjacent folds, and the folded structure including the substantially triangular structure has a continuous folded structure while being inverted.
[0082] Next, the carbon fiber nonwoven fabric was coated with resin (A) having a basis weight of 200 g / cm 2 The PP resin film was laminated and then hot-pressed. In the hot-press process, the mold temperature was 180°C and pressure was 3 MPa for 10 minutes to impregnate the carbon fiber nonwoven fabric with the PP resin, resulting in a prepreg with a side length of 200 mm.
[0083] A fiber-reinforced composite material was molded by heating and expanding one sheet of the obtained prepreg for 10 minutes using a press molding machine adjusted to a mold temperature of 180°C and a molded product thickness of 2.8 mm. The obtained fiber-reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in Figure 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0084] [Example 6] Two sheets of the prepreg obtained in Example 1 were laminated to form a preform, which was heated for 10 minutes using a press molding machine adjusted so that the mold temperature was 180°C and the molded product thickness was 4.8 mm, to mold a laminated fiber-reinforced composite material. The obtained fiber-reinforced composite material had a cross-sectional opening of a coarse pore surrounded on three sides by a micropore as shown in Figure 8, and had a structure in which this was laminated in two layers. The cross-sectional openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0085] [Example 7] As the reinforcing fiber substrate (B), a folded substrate similar to that in Example 1 was used, and as the resin (A), a fiber having a basis weight of 200 g / cm 2 The PA resin film was laminated and hot-pressed. In the hot-pressing process, the carbon fiber nonwoven fabric was impregnated with the PA resin by pressing for 10 minutes at a mold temperature of 260°C and a pressure of 3 MPa to obtain a prepreg with a side of 200 mm. One sheet of the obtained prepreg was heated and expanded for 10 minutes using a press molding machine adjusted to a mold temperature of 260°C and a molded product thickness of 2.8 mm, to mold a fiber-reinforced composite material. The obtained fiber-reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in FIG. 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0086] [Example 8] As the reinforcing fiber substrate (B), a folded substrate similar to that in Example 1 was used, and as the resin (A), a fiber having a basis weight of 200 g / cm 2The PPS resin film was laminated and hot-pressed. In the hot-pressing process, the PPS resin was impregnated into the carbon fiber nonwoven fabric by pressing at a mold temperature of 300°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side of 200 mm. One sheet of the obtained prepreg was heated and expanded for 10 minutes using a press molding machine adjusted to a mold temperature of 300°C and a molded product thickness of 2.8 mm, to mold a fiber-reinforced composite material. The obtained fiber-reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in Figure 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0087] [Example 9] As the reinforcing fiber substrate (B), a folded substrate similar to that in Example 1 was used, and as the resin (A), a fiber having a basis weight of 200 g / cm 2 The PEKK resin film was laminated and hot-pressed. In the hot-press process, the PEKK resin was impregnated into the carbon fiber nonwoven fabric by pressing at a mold temperature of 350°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side of 200 mm. One sheet of the obtained prepreg was heated and expanded for 10 minutes using a press molding machine adjusted to a mold temperature of 350°C and a molded product thickness of 2.8 mm, to mold a fiber-reinforced composite material. The obtained fiber-reinforced composite material had an opening with a cross section of approximately triangular shape surrounded on three sides by micropores as shown in Figure 8. The openings of the coarse pores were aligned in the in-plane direction. The evaluation results are shown in Table 1.
[0088] [Example 10] The fiber reinforced composite material obtained in Example 1 was used as a core layer, and the thermosetting prepreg prepared as above was arranged on the outside of the core layer as a skin layer, and the orientation direction of the reinforcing fibers on the surface of one of the skin layers was set as 0° as a reference, and the laminated structure was [0° / 90° / fiber reinforced composite material / 90° / 0°]. Next, the thermosetting prepreg was cured by hot pressing at a mold temperature of 150°C and a pressure of 1 MPa for 10 minutes, and a sandwich structure was obtained. The thickness of the fiber reinforced composite material in the obtained sandwich structure was 2.4 mm, and it was able to be used well as a core layer without being crushed when forming a sandwich structure.
[0089] [Example 11] The fiber-reinforced core material of the laminate obtained in Example 6 was used as a core layer, and a thermosetting prepreg was arranged on the outside of the core layer as a skin layer, and the orientation direction of the reinforcing fibers on the surface of one of the skin layers was set as 0° as a reference, and the laminate structure was laminated so that it was [0° / 90° / fiber-reinforced composite material / 90° / 0°]. Next, the thermosetting prepreg was cured by hot pressing at a mold temperature of 150°C and a pressure of 1 MPa for 10 minutes, and a sandwich structure was obtained. The thickness of the laminate in the obtained sandwich structure was 4.3 mm, and it could be used well as a core layer without being crushed when making a sandwich structure.
[0090] [Comparative Example 1] The carbon fiber nonwoven fabric is folded regularly over the entire prepreg so that it has a cross-sectional structure with vertices 8 of a zigzag structure as shown in FIG. 11. The basis weight is 100 g / cm. 2 A base material having a basis weight of 200 g / cm was prepared. At this time, creases were made so that the repeat interval 9 between the apexes of the zigzag structure was 5 mm at equal intervals. 2 A PP resin film of the above was laminated on the substrate and hot-pressed. In the hot-press process, the substrate was impregnated with the PP resin by applying pressure at a mold temperature of 180°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg having a side of 200 mm. One sheet of the obtained prepreg was heated and expanded for 10 minutes using a press molding machine adjusted to a mold temperature of 180°C and a molded product thickness of 2.8 mm, to form a fiber-reinforced composite material. The cross section of the microporous portion 11 of the obtained fiber-reinforced composite material had a zigzag structure as shown in FIG. 13. The evaluation results are shown in Table 2.
[0091] [Comparative Example 2] Flat and uncreased 100g / cm 2 The carbon fiber nonwoven fabric has a basis weight of 200g / cm 2The PP resin film was laminated and hot-pressed. In the hot-press process, the PP resin was impregnated into the substrate by pressing at a mold temperature of 180°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side of 200 mm. A fiber-reinforced composite material was molded by heating and expanding one sheet of the obtained prepreg for 10 minutes using a press molding machine with a mold temperature adjusted to 180°C. The distance between the upper and lower dies of the mold was set to 2.8 mm, and the molded product was molded to a thickness of 2.8 mm, but the prepreg did not expand to the thickness between the upper and lower dies of the mold, and the thickness of the obtained fiber-reinforced composite material remained at 0.9 mm. The evaluation results are shown in Table 2.
[0092] [Comparative Example 3] Flat and uncreased 100g / cm 2 The carbon fiber nonwoven fabric has a basis weight of 200g / cm 2 The PA resin film was laminated and hot-pressed. In the hot-press process, the substrate was impregnated with the PA resin by applying pressure at a mold temperature of 260°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side of 200 mm. A fiber-reinforced composite material was molded by heating and expanding one sheet of the obtained prepreg for 10 minutes using a press molding machine with a mold temperature adjusted to 260°C. The distance between the upper and lower dies of the mold was set to 2.8 mm, and the molded product was molded to a thickness of 2.8 mm, but the prepreg did not expand to the thickness between the upper and lower dies of the mold, and the thickness of the obtained fiber-reinforced composite material remained at 0.8 mm. The evaluation results are shown in Table 2.
[0093] [Comparative Example 4] Flat and uncreased 100g / cm 2 The carbon fiber nonwoven fabric has a basis weight of 200g / cm 2The PPS resin film was laminated and hot-pressed. In the hot-press process, the substrate was impregnated with the PPS resin by applying pressure at a mold temperature of 300°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side of 200 mm. A fiber-reinforced composite material was molded by heating and expanding one sheet of the obtained prepreg for 10 minutes using a press molding machine with a mold temperature adjusted to 300°C. The distance between the upper and lower dies of the mold was set to 2.8 mm, and the molded product was molded to a thickness of 2.8 mm, but the prepreg did not expand to the thickness between the upper and lower dies of the mold, and the thickness of the obtained fiber-reinforced composite material remained at 0.4 mm. The evaluation results are shown in Table 2.
[0094] [Comparative Example 5] Flat and uncreased 100g / cm 2 The carbon fiber nonwoven fabric has a basis weight of 200g / cm 2 The PEKK resin film was laminated and hot-pressed. In the hot-press process, the PEKK resin was impregnated into the substrate by applying pressure at a mold temperature of 350°C and a pressure of 3 MPa for 10 minutes to obtain a prepreg with a side length of 200 mm. A fiber-reinforced composite material was molded by heating and expanding one sheet of the obtained prepreg for 10 minutes using a press molding machine with a mold temperature adjusted to 350°C. The distance between the upper and lower dies of the mold was set to 2.8 mm, and the molded product was molded to a thickness of 2.8 mm, but the prepreg did not expand to the thickness between the upper and lower dies of the mold, and the thickness of the obtained fiber-reinforced composite material remained at 0.6 mm. The evaluation results are shown in Table 2.
[0095] [Comparative Example 6] The fiber reinforced composite material obtained in Comparative Example 1 was used as a core layer, and a thermosetting prepreg was arranged on the outside of the core layer as a skin layer. The orientation direction of the reinforcing fibers on the surface of one of the skin layers was set as 0°, and the laminated structure of the thermosetting prepreg was [0° / 90° / fiber reinforced composite material / 90° / 0°]. The thermosetting prepreg was then cured by hot pressing at a mold temperature of 150°C and a pressure of 1 MPa for 10 minutes to obtain a sandwich structure. The thickness of the fiber reinforced composite material in the obtained sandwich structure was 0.6 mm, and it was crushed by the molding pressure to form the sandwich structure, and could not be used as a core layer.
[0096] [Table 1]
[0097] [Table 2] [Industrial Applicability]
[0098] Fiber-reinforced composite materials obtained by molding the prepreg of the present invention can be suitably used for aircraft structural members, wind turbine blades, automobile structural members, IC trays, notebook computer housings, and the like. [Explanation of symbols]
[0099] 1 Prepreg 2. Resin (A) 3 Reinforcement fiber or reinforcing fiber substrate (B) 31 Folds in reinforcing fibers or folds in reinforcing fiber substrate (B) 31A Fold of reinforcing fiber base material (B) (first fold) 31B Fold of reinforcing fiber base material (B) (second fold) 31C Fold of reinforcing fiber base material (B) (third fold) 31D Fold of reinforcing fiber base material (B) (fourth fold) Lr: Distance between the first fold and the nearest fold (fourth fold) Lf: The distance from the first fold to the fold closest to the first fold (the fourth fold) along the reinforcing fiber base material (B) θ Fold angle 4. Space with an approximately triangular cross section (large void) 5 Microporous structure 6 A pair of adjacent folds in the reinforcing fiber substrate (B) 7. The composition ratio of a pair of adjacent folds when viewed on both sides of a folded substrate 8. Zigzag structure apex 9. Repeat interval between vertices of a zigzag structure 10 Space with a roughly trapezoidal cross section (large void) 11 Microporous section
Claims
1. A prepreg in which a reinforcing fiber substrate (B) is impregnated with a resin (A), The reinforcing fiber base material (B) is present in a folded state having a plurality of folds with fold angles of 0° or more and less than 90° in the prepreg, and the reinforcing fiber base material (B) is present in a folded state including a substantially triangular structure formed by the first fold and one of the fourth folds being close to each other, when an arbitrarily selected fold in a cross section perpendicular to the direction of the folds is defined as a first fold, a fold adjacent to the first fold is defined as a second fold, a fold further adjacent to the second fold is defined as a third fold, and a fold further adjacent to the third fold is defined as a fourth fold.
2. In the cross section of the reinforcing fiber base material (B) perpendicular to the direction of the fold, when the straight-line distance between the first fold and the fourth fold closest to the first fold is Lr, and the distance from the first fold to the fourth fold closest to the first fold along the reinforcing fiber base material (B) is Lf, Lr / Lf is 0.3 or less and Lf is 1 mm or more and 200 mm or less. The prepreg according to claim 1.
3. The reinforcing fiber base material (B) is in a folded state including a Z-shaped structure having the first fold and one of the second folds adjacent to the first fold as bending points in a cross section perpendicular to the direction of the fold. The prepreg according to claim 1 or 2.
4. The prepreg according to claim 3, wherein the reinforcing fiber substrate (B) is in a folded state including a structure in which the Z-shaped structure is continuous in a cross section perpendicular to the direction of the fold.
5. The reinforcing fiber base material (B) has a continuous folded structure in which a folded structure including the approximately triangular structure is inverted in a cross section perpendicular to the fold direction. Prepreg according to any one of claims 1 to 4.
6. The prepreg according to any one of claims 1 to 5, wherein the reinforcing fiber base material (B) has a regular folded structure throughout the prepreg.
7. The prepreg according to any one of claims 1 to 6, wherein the reinforcing fiber base material (B) is a nonwoven fabric composed of discontinuous reinforcing fibers.
8. The prepreg according to any one of claims 1 to 7, wherein the resin (A) is a thermoplastic resin.
9. A preform obtained by laminating the prepregs according to any one of claims 1 to 8.
10. A fiber-reinforced composite material obtained by molding the prepreg according to any one of claims 1 to 8 or the preform according to claim 9.
11. A sandwich structure comprising the fiber-reinforced composite material according to claim 10 sandwiched between skin layers.
12. A method for producing the prepreg according to any one of claims 1 to 8, comprising the steps of: Step [1]: A step of folding the reinforcing fiber substrate (B) into a folded state having a plurality of folds with folding angles of 0° or more and less than 90°; Step [2]: A step of compounding the resin (A) with the reinforcing fiber substrate (B) in a folded state; A method for producing a prepreg having the above-mentioned components in this order.
13. A method for producing a fiber-reinforced composite material, comprising heating the prepreg according to any one of claims 1 to 8 or the preform according to claim 9 to a temperature equal to or higher than the temperature at which the resin (A) melts or softens, and molding the prepreg.
Citation Information
Patent Citations
JP1982102536U
Foldable core with high compression ratio and articles manufactured therefrom
JP2012500864A
Foldable cores based on carbon fiber paper and articles made therefrom
JP2013511629A
Composite structure and method for manufacturing same
WO2018117181A1
Preform element, preform using same, and method for producing same
WO2018147324A1